Relación entre alteraciones cráneo-cervicales y maloclusión esquelética en pacientes entre los 8 y 11 años de edad que asisten a las clínicas de la universidad Antonio Nariño sede Armenia (2021)
Skeletal malocclusion is one of the most frequent alterations found in the daily diagnosis during the care of pediatric patients and its correction has become an important part of the comprehensive care of growing patients, where it has been possible to show the close relationship between body posture, craniocervical and mandibular position, based on the bibliographic review carried out, studies were found that relate skeletal malocclusions with craniocervical posture, which is why the relationship between malocclusion with cranio-cervical posture is proposed as an object of study.